Effect of immobilization protocol on optimal conditions of ethyl butyrate synthesis catalyzed by lipase B from Candida antarctica - Friedrich, John L. R.; Peña, Fernanda P.; García-Galán, Cristina; Fernández-Lafuente, Roberto; Ayub, Marco A. Z.; Rodrigues, Rafael C. (Journal of Chemical Technology & Biotechnology, 2013)
[Background] In this work two immobilized preparations of lipase (EC 3.1.1.3) B from Candida antarctica (CALB) were compared as biocatalysts in the synthesis of ethyl butyrate, a short‐chain esters with fruity notes. Commercial Novozym 435 and CALB immobilized on styrene‐divinylbenzene beads (MCI‐CALB) were tested for esterification reactions. Central composite design and response surface methodology were used to optimize the reaction temperature, substrate molar ratio, enzyme content, and the added water. [Results] The two enzymatic preparations presented different optimal conditions concerning ethyl butyrate production, with higher yields of conversion around 85% in 1.5 h being achieved. However, MCI‐CALB presented productivities 1.6 times higher than Novozym 435. The main difference between the biocatalysts was in relation to operational stability during batch reuse experiments, in which MCI‐CALB retained 80% of its initial activity after eight batches, while Novozym 435 retained only 20% under the same conditions. [Conclusion] It was verified that variations in the protocols for enzyme immobilization causes different optimal conditions for the esterification reaction. These are very interesting results because reaction times were short, producing high conversion yields and productivities considering the mass of biocatalyst used. This work was supported by grants from Fundação de Amparo a Pesquisa do Rio Grande do Sul (FAPERGS – ARD/2011) and CTQ2009‐07568 from Spanish Ministerio de Ciencia e Innovación. We also thank Ministerio de Ciencia e Innovación for a fellowship for C. Garcia‐Galan and Conselho Nacional de Desenvolvimento Científico Tecnológico (CNPq ‐ Brazil) for a fellowship to J. L. R. Friedrich. Peer Reviewed